The Minimum Stimulus Conditions for Vection—Two- and Four-Stroke Apparent Motions Can Induce Self-Motion Perception. (February 2013) - Nakamura, Shinji
Vection can be induced by repeated presentation of static visual images with only two or four frames. The result suggests that vection is only affected by the perceived motion of the visual stimulus, not by awareness of visual displacement.